2020
DOI: 10.1021/acsaem.0c02157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Niobium Doping Concentration on the Charge Storage Mechanism of Mesoporous Anatase Beads as an Anode for High-Rate Li-Ion Batteries

Abstract: A promising strategy to improve the rate performance of Li-ion batteries is to enhance and facilitate the insertion of Li ions into nanostructured oxides like TiO 2 . In this work, we present a systematic study of pentavalent-doped anatase TiO 2 materials for third-generation high-rate Li-ion batteries. Mesoporous niobium-doped anatase beads (Nb-doped TiO 2 ) with different Nb 5+ doping (n-type) concentrations (0.1, 1.0, and 10% at.) were synthesized via an improved template approach followed by hydrothermal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Production of Nb-doped TiO 2 has been proposed by sol–gel synthesis, for example, for anatase beads with 0.1–10 atom % Nb from starting material of titanium(IV) isopropoxide with 1-hexadecylamine as a structure-directing agent for use in Li-ion batteries. 20 A similar sol–gel synthesis of TiO 2 doped with about 10% Nb from titanium tetrabutyl titanate with 1-hexadecylamine and polydimethylsiloxane as structure determining agents was prepared for use in electrorheological fluids. 39 A sol–gel preparation followed by spark plasma sintering with repeated oxidation and reduction is another method proposed for the preparation of Nb-doped TiO 2 powders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of Nb-doped TiO 2 has been proposed by sol–gel synthesis, for example, for anatase beads with 0.1–10 atom % Nb from starting material of titanium(IV) isopropoxide with 1-hexadecylamine as a structure-directing agent for use in Li-ion batteries. 20 A similar sol–gel synthesis of TiO 2 doped with about 10% Nb from titanium tetrabutyl titanate with 1-hexadecylamine and polydimethylsiloxane as structure determining agents was prepared for use in electrorheological fluids. 39 A sol–gel preparation followed by spark plasma sintering with repeated oxidation and reduction is another method proposed for the preparation of Nb-doped TiO 2 powders.…”
Section: Resultsmentioning
confidence: 99%
“… 12 Other catalytic applications are for catalyst supports, 13 for example, for the oxygen reduction reaction 14 and H 2 production, 15 or for dimensionally stable anodes for the chlorine evolution reaction, 16 and electrochemical destruction of “forever chemicals”. 17 Nb-doped TiO 2 has potential application in batteries and supercapacitors 18 including lithium-ion batteries 19 , 20 and Na-ion batteries. 21 Other potentials uses are for CO sensing 22 and thermoelectric power production.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, sodiation can change the electronic properties from insulating to metallic. [273] DFT simulations showed that a Nb concentration of 0.1-1.0% increased the metallic character of TiO 2 due to the induced shift in Fermi level upon doping, whilst retaining the redox properties of the undoped anatase, [274] whereas the semiconducting Na 2 Ti 3 O 7 with bandgap 2.25 eV becomes metallic upon full sodiation. [273] The role of functionalization is not limited to voltage and surface adsorption though, and can be employed as a materials design tool to also modify mobility.…”
Section: Insertion-type Anodesmentioning
confidence: 99%
“…It is well known that the effects related to surface charge are more noticeable at high scan rate analysis. 25,49 A possibility is to attribute this overall charge capacitance effect to the surface effect associated with the presence of LSPRs in the doped NCs, something we will address later. Moreover, looking at the CVs in detail (inset graphs Fig.…”
Section: Doping Effect In the Electronic And Crystalline Structuresmentioning
confidence: 99%